Estudo de variáveis termo-higrométricas em parque urbano na cidade de Cuiabá - MT - Tocantins, Ivan (2019)
Micrometeorological and climatic conditions are crucial for any location, and from the point of view of decent living, especially in terms of hygrothermal comfort, is certainly the main one. The response of our sensations to the conditions of atmospheric temperature and humidity is instantaneous and every few seconds. In Cuiabá, these two factors are always exacerbated and, at some times and in some years when there is interaction with other factors of greater regional and global scale, the capital's habitable condition borders on the unimportant, causing the community to seek and plead for the taking. mitigating measures regarding this discomfort, as measures of elimination or even reduction are impracticable given the prevailing magnitude of nature. This research aims to analyze the thermohygrometric variables in Parque Zé Bolo Flô, a state conservation unit inserted in the urban area of Cuiabá. In the methodology employed, we collected collections by mobile transects that were walked by with thermo-hygrometric data collection in sixteen points of the park, from June 2016 to May 2017, in the early morning and afternoon, during three months. consecutive days of each month and covered the two characteristic seasons of the Midwest, both warm, one dry and the other wet. It was evidenced that the forcing of the massive urbanization and the consequent subtraction of vegetation, previously dampening the thermohygrometric effects around the park, culminate in the increase of thermal energy to the environment. The vegetated region of the park presented discrete characteristic of microclimate, slightly different and attenuated in relation to the surroundings, especially in the hot-humid period. The modest scale of the park's area in relation to the southern region to which it belongs, especially when compared to the urban surface of the Capital, although it does not fit the anomalies, at least from the point of view of collections and thermohygrometric sensations. is of your moderate attenuation. It is up to the city planners and managers, as well as the urban community, to consider these mitigating measures for immediate and massive replacement of trees throughout Cuiabá so that this benefit of hygrothermal improvement evidenced on a microclimate scale in urban parks can be expanded and felt.